Edukasi Gizi Jajanan Sehat Anak Sekolah SD 07 Kramat Pela Jakarta Selatan - Anastu Regita Nareswara; Rosmida Magdalena Marbun; Meilinasari; Reni Chairani; Muntikah (CV. Multi Kreasi Media, 2025)
Primary school children are a vulnerable age group that requires adequate nutritional intake to support physical growth and cognitive development. However, many children do not bring snacks from home and choose to buy snacks in the school environment, which often do not meet safety and nutrition standards. This study aims to improve the knowledge of students in grades 4-6 at SDN 07 Kramat Pela, Kebayoran Baru, South Jakarta, about healthy snacks through counseling. The methods used were lectures and question and answer discussions, followed by anthropometric measurements, pretest, posttest, and distribution of healthy snacks. This activity involved 35 students and showed an increase in knowledge about healthy snacks, with the percentage of students who had very good knowledge increasing from 68% before counseling to 82% after counseling. These results are in line with previous research that shows the importance of knowledge about healthy food as an internal factor that affects the consumption of healthy snacks. Thus, counseling on healthy snacks is expected to increase students' awareness and understanding of the importance of choosing nutritious and safe food for their health.